1991
DOI: 10.1088/0953-8984/3/12/020
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance and electron-nuclear double-resonance investigation of a new Cr3+defect on an Nb site in LiNbO3:Mg:Cr

Abstract: For LiNb03 crystals heavily doped with Mg and codoped with Cr a single isotropic ~~~l i n e w i t h g = 1.971 t 0.002andaminimallinewidthof 1.8 f 0.2 mThasbeenobserved. With ENDOR it could be shown unambiguously that the new defect is C3' substituting for Nb. The 53Cr hyperfine and quadrupole constants are A,, = 50.8 2 0.2 MHz, A, = 51.0 rt 0.2 MHz and P = 0.10 rt 0.05 MHz. The crystal field at the chromium site is smaller by more than an order of magnitude than for previously reported Cr3+ centres in LiNb03, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…In the rhombohedral (space group R3c) lattice of LiNbO 3 the cations Li + and Nb 5+ are surrounded by 6 oxygen ions forming trigonally distorted octahedrons. Present interpretation (see for example [4]) based on ESR data [10-12 and Nb ) in the LiNbO 3 lattice, which was confirmed by ESR and ENDOR studies [13][14][15]. Above that Mg concentration threshold the samples change their color from green to pink due to a strong red shift of broad band transitions 4 [4,15].…”
supporting
confidence: 61%
“…In the rhombohedral (space group R3c) lattice of LiNbO 3 the cations Li + and Nb 5+ are surrounded by 6 oxygen ions forming trigonally distorted octahedrons. Present interpretation (see for example [4]) based on ESR data [10-12 and Nb ) in the LiNbO 3 lattice, which was confirmed by ESR and ENDOR studies [13][14][15]. Above that Mg concentration threshold the samples change their color from green to pink due to a strong red shift of broad band transitions 4 [4,15].…”
supporting
confidence: 61%
“…This is confirmed by the EPR signal with an almost isotropic-factor, g ¼ 1.97, associated with this center [5]. Under the influence of 514.5 nm argon-ion laser line, the intensity of this signal diminishes strongly (even up to several %, depending on intensity of the illumination).…”
Section: Cr 3+mentioning
confidence: 52%
“…Certain models of the Cr 3+ Nb in LiNbO 3 :MgO crystals have been proposed by Yang et al [4] Existence of the Cr 3+ Nb centers has also been observed in EPR experiments. They are characterized by an almost isotropic EPR signal, very characteristic for LiNbO 3 :Cr,MgO pink colored samples containing such centers [5]. No direct identification of the EPR signal with particular Cr Nb centers observed in optical experiment has been made.…”
Section: Introductionmentioning
confidence: 99%
“…17 For Mg-codoped ͑over the 5-6 mol % threshold͒ crystals, an at least partial change of the substitution site from the Li ϩ to the Nb 5ϩ site has been predicted for dopant cations with larger valences. 18,8 This has been experimentally verified for the Hf dopant 19,20 that is isoelectronic with Ti, and also for Cr 3ϩ ions [21][22][23] and Fe 3ϩ ions. 24,25 Therefore, we tentatively attribute the observed EPR signal to Ti 3ϩ on the Nb site.…”
Section: Discussionmentioning
confidence: 74%